Crecimiento Pre-Destete del Ovino F1 Blackbelly x Pelibuey en Condiciones de Pastoreo Libre en la Amazonía Ecuatoriana - Moyano, Juan Carlos (2017)
The aim of this study was to describe the growth curves of F1 Blackbelly x Pelibuey sheep from birth to weaning under free grazing conditions in the Ecuadorian Amazon. Twelve males and 10 females were used in the study. The animals were weighed at birth, at 4 and 9 days of age and then weekly until 55 days of age (weaning). Body development was linear. There were no significant differences in birth weight, weaning weight and daily weight gain between sexes.